2009
DOI: 10.1111/j.1365-3059.2009.02146.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the host range of the barley strain of Wheat dwarf virus using an agroinfectious viral clone

Abstract: Comparative analysis of the host ranges of the barley and wheat strains of Wheat dwarf virus (WDV; family Geminiviridae; genus Mastrevirus) in Europe has been severely hampered by the lack of an infectious clone of the barley strain. To remedy this situation an agroinfectious clone of a Hungarian isolate of the barley strain (WDV-Bar[HU]) was constructed and its virulence tested in barley (Hordeum vulgare), wheat (Triticum aestivum), rye (Secale cereale) and oat (Avena sativa) by agroinoculation. Although all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…For example, whereas the ''A'' strain of MSV is clearly the only group of MSV variants that cause severe disease in maize [37,58], the ''A'' strain of WDV preferentially infects barley, whereas the ''C'' strain preferentially infects wheat [50].…”
Section: Rational Mastrevirus Species and Strain Demarcation Criteriamentioning
confidence: 99%
“…For example, whereas the ''A'' strain of MSV is clearly the only group of MSV variants that cause severe disease in maize [37,58], the ''A'' strain of WDV preferentially infects barley, whereas the ''C'' strain preferentially infects wheat [50].…”
Section: Rational Mastrevirus Species and Strain Demarcation Criteriamentioning
confidence: 99%
“…A great emphasis has been emerged here stressed on the biological difference between the viral isolates would be classified into different strains. For example, whereas the ''A'' strain of MSV is clearly the only group of MSV variants that cause severe disease in maize [28,42], the ''A'' strain of WDV favourably infects barley, whereas the ''C'' strain preferentially infects wheat [39], our Egyptian isolate of CpCDV could be assigned as a specific strain preferentially infects squash which is essentially a non-host species of this virus. Through recombination analysis performed using RDP4, it has been observed that the Egyptian isolate although more closely related to the Syrian isolate but a considerable part of the genome found to be originated from a different isolate of BeYDV assigned in the genbank under accession no ENA|DQ458791 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic and control plantlets were used for virus infection studies. To mimic the real field infection process, WDV-infected barley plants were produced by Agrobacterium-mediated delivery of the agroinfectious WDV clone into barley (Ramsell et al, 2009). Then, the generated WDVinfected plants were used to feed the collected and propagated leafhoppers.…”
Section: Transgenic Barley Lines and Resistance Phenotyping Followingmentioning
confidence: 99%
“…The virion-sense V1 and V2 open reading frames (ORFs) encode the viral movement protein (MP) and coat protein (CP), whereas the other two ORFs, C1 and C2, located on complementary-sense, encode Rep and RepA proteins, respectively, associated with virus replication (Boulton, 2002). WDV is a pathogen of both wheat and barley, associated with chlorosis, severe stunting and even plant decline, causing severe yield losses in many countries (Ramsell et al, 2009). There are two main types of WDV strain, barley and wheat strains, sharing approximately 84% nucleotide identity, which are able to infect the other host with low efficiency (Koklu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%